IMPLEMENTASI PEMBERDAYAAN MANAJEMEN LATIHAN MENEMBAK TERHADAP PENINGKATAN KEMAMPUAN PRAJURIT AKADEMI MILITER - Sopiin; Aris Basuki; Yulianto; Ari Kristanto (JURNAL MAHATVAVIRYA, 2023)
For improving the quality of human resources, it is necessary to train the unit/Binsat which is programmed through the management of training techniques in the unit in a systematic, gradual, multilevel and continuous manner, so that the knowledge and skills of soldiers can be maintained and can even be improved so that the mission/tasks of the unit can be carried out effectively and efficiently in achieving the main tasks of the Military Academy according to the purpose of research to determine the technique of training/Nikgarlat. Implementation of Exercise Management in the army can be evaluated in a measurable and accountable we use qualitative research methods that include goals and objectives. The results of the implementation of the exercise, before and after training were compared to determine the technique of conducting training on changes in the level of shooting ability of each soldier. This step is important because the goal of exercise management is to change the behavior or level of ability in the achievement of soldiers towards improvement through planned methods and approaches. Technical organizer of Binsat is at the Director of the Institution as one of the implementing units of the Military Academy which has a very strategic role in supporting the educational operations of the Akmil cadets, especially in organizing demonstrations and training demonstrations as well as the support of shooting trainers who are practical according to the standard level of ability. Of training management has been able to maintain and improve the level of proficiency both individually and positions in the unit, based on the results of data collection and analysis of the results of the conclusion of the Jatri shooting training products, in principle the training has been carried out correctly and the effectiveness in training management is comparable to the standard of BPUJ and BPKJ training result, but the achievement of Target results in terms of the quantity of the level of training capability has not been evenly distributed due to assignment factors, munitions support in the standard level of capability needs to be driilnis and dry shooting.